1944
DOI: 10.1021/ie50419a012
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization of Saturated Acrylic Resins

Abstract: Rubberlike materials, designated as Lactoprene, were prepared In earlier investigations by copolymerizing ethyl acrylate with small proportions of butadiene, Isoprene, or allyl maleate, compounding the resulting copolymers (assumed to have olefinic unsaturation) with sulfur and accelerators, and then curing the compounded products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1948
1948
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Pale crepe, rvhich is considered to have nearly 100% internal double bonds, appears to contain 10-15% vinyl double bonds following oxidative break-down (17). However, successful ozonolysis studies have been reported for 50-50 butadiene-styrene copolymers (1), alkali metal catalyzed polybutadiene (22), and GR-S (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pale crepe, rvhich is considered to have nearly 100% internal double bonds, appears to contain 10-15% vinyl double bonds following oxidative break-down (17). However, successful ozonolysis studies have been reported for 50-50 butadiene-styrene copolymers (1), alkali metal catalyzed polybutadiene (22), and GR-S (17).…”
Section: Discussionmentioning
confidence: 99%
“…(16) Meyer, Hans, "Nachwels und Bestimmung Organischer Verbindungen," p. 127, Berlin, J. Springer, 1933. (17) Mikusch, J. D. xron, J. Am.…”
Section: (1940)unclassified
See 1 more Smart Citation
“…Many curative systems for saturated polyacrylic elastomers are reported in the literature. Some of these are metallic oxides (6), polyamines (7), dioximes(8), peroxides (8), and sodium metasilicate (5,9). Table II summarizes the data obtained in studies to adapt these systems to Vyram polyacrylic elastomer.…”
Section: Vulcanizationmentioning
confidence: 99%
“…of acrylic esters and dienes such as butadiene have been found (8,8) capable of undergoing vulcanization with sulfur and certain accelerators. It was observed subsequently (6,8) that halogen-containing acrylic resins, prepared conveniently (9) by copolymerizing 95 parts of ethyl acrylate with approximately 5 parts of either 3-chloropropyl acrylate or 2-chloroethyl acrylate, also can be vulcanized with sulfur and with certain other agents.…”
Section: Copolymersmentioning
confidence: 99%